Clinical Outcome and Cost-Effectiveness Analysis of CSII Versus MDI in Children and Adolescent With Type 1 Diabetes Mellitus in a Public Health Care System of China - Hu, Sicui; Yang, Hongxiu; Chen, Zhihong; Leng, Xuefei; Li, Cheng; Qiao, Lingyan; Lv, Weiqing; Li, Tang (Frontiers in Endocrinology, 2021)
Objectives: To evaluate the clinical and economic consequences of CSII vs MDI in children and adolescents with type 1 diabetes mellitus (T1DM) from a public health care system in developed areas of developing country. Methods: This was a retrospective cohort study of children and adolescents with T1DM. Data were collected at baseline and the end of every year including glycated hemoglobin (HbA1c), insulin dose, lipid proﬁle，blood pressure and adverse events (severe hypoglycemia and DKA). In the CSII group, the subjects were divided into three different age groups (below six, six to twelve, thirteen to eighteen). The Cost-effectiveness analysis was performed using the IQVIA CORE Diabetes Model (CDM) to simulate diabetes progression by utilising the clinical data obtained from the two groups. The main outcome measures were Life Expectancy, Quality adjusted life years（QALYs）, Total Costs and Incremental Costs and Effectiveness Ratio (ICER) of CSII compared with MDI in Chinese pediatric patients with T1DM in Qingdao City (60 years). Results: Mean HbA1c values and daily insulin doses were significantly lower in those receiving CSII therapy throughout follow-up. When cases were stratified by age within the CSII group, the insulin doses used by subjects aged over 12 years was higher than that in the other age groups and the improvement in HbA1c was most significant in the over 12 years old group. Mean direct lifetime costs were ¥ 67,137 higher with CSII treatment than with MDI for pediatric patients. Treatment with CSII was associated with an improvement in life expectancy of 0.41 years for pediatric patients compared with MDI based on CORE diabetes model simulation. The corresponding gains in QALYs were 0.42. These data produced corresponding ICER is ¥ 161,815 per QALY for pediatric T1DM patients in Qingdao.Sensitivity analyses suggested that our base-case assumptions were mostly robust. Conclusions: CSII is associated with improved long‐term clinical outcomes compared with MDI. Based on this model analysis, CSII appears to be more cost-effective for the Qingdao TIDM pediatric population and health care system.